Potensi Antibakteri Kombinasi Ekstrak Daun Mangga (Mangifera indica L.) dan Daun Kirinyuh (Chromolaena odorata L.) Terhadap Staphylococcus aureus - Syarah Anliza; Deisya Tyas Marwin; Nurmeily Rachmawati; Hamtini (Journal of Medical Laboratory Research, 2025)
Infectious diseases caused by Staphylococcus aureus are one of the health problems occurring in Indonesia. Infectious diseases can be treated with antibiotics. However, antibiotics used without proper prescription can trigger antibiotic resistance. To overcome antibiotic resistance, a combination of natural ingredients such as kirinyuh leaves (Chromolaena odorata L.) and mango leaves (Mangifera indica L.) can be used. This study aims to determine the inhibitory activity and effective concentration of the combination of mango leaves extract (Mangifera indica L.) and kirinyuh leaves  extract (Chromolaena odorata L.) as antibacterial agents against Staphylococcus aureus. The methods used in this study included maceration to prepare mango leaves and kirinyuh leaves extract, phytochemical screening to identify the presence of secondary metabolites in the kirinyuh leaves and mango leaves extract, and the disk diffusion method for antibacterial testing. The results showed inhibitory activity at all concentrations due to the presence of secondary metabolites in the kirinyuh leaves and mango leaves extracts. At a 1:3 concentration, an inhibition zone of 18 mm was obtained; at a 1:1 concentration, an inhibition zone of 19 mm was obtained; at a 3:1 concentration, an inhibition zone of 20 mm was obtained. The effective concentration of the combination as an antibacterial agent is the 3:1 concentration. The results of this study fall into the strong category, indicating that the combination of mango leaves and kirinyuh leaves extracts has antibacterial efficacy against Staphylococcus aureus.